Taxpayer Objection Efforts in Urban Land and Building Tax (PBB-P2) Dispute (Case Study At the Regional Revenue Agency of Madiun City) - Andyka Yuliatama A; Aidul Fitriciada Azhari; Nuria Siswi Enggarani (Jurnal Indonesia Sosial Teknologi, 2024)
The Madiun City Government is facing problems in resolving tax issues, which can be resolved through standard tax objection resolution. The legal basis used is Law No. 28 of 2009 concerning Regional Taxes and Regional Levies. BAPENDA Madiun City has the authority to manage land and building taxes based on these regulations. This research aims to determine legal efforts in filing objections to resolving tax disputes in the PBB-P2 field and the obstacles taxpayers face in making legal objections. The research method used is the normative legal research method. The research results state that taxpayers who feel that the NJOP value determined by Bapenda is not by the condition of their property can submit an appeal to the Tax Court Agency. The process begins with submitting an objection letter to Bapenda within a certain period after sending the tax notification. If the objection is not accepted, the taxpayer can appeal to the Tax Court Agency. However, in the case at the Madiun City Bapenda, the request for an objection to the NJOP value of land and buildings was not granted. There are several obstacles to legal action for taxpayers' objections to resolving tax disputes in the urban PBB sector in Madiun City, such as legal uncertainty and limitations of law enforcement agencies. Legal reform, increasing the capacity of law enforcement agencies, and increasing awareness of tax law among the public are needed to overcome this.